Super sensational science fair projects - Dispezio, Michael A.; Toye, Derek, ill. (New York : Scholastic, 2003)
Provides help in creating and carrying out a science project by presenting an actual sample project, along with specific project ideas and strategies.
Includes index.
Keywords: Science projects -- Juvenile literature